Role of the clathrin adaptor PICALM in normal hematopoiesis and polycythemia vera pathophysiology - Yuichi Ishikawa; Manami Maeda; Mithun Pasham; Francois Aguet; Silvia K. Tacheva-Grigorova; Takeshi Masuda; Hai Yi; Sung-Uk Lee; Jian Xu; Julie Teruya-Feldstein; Maria Ericsson; Ann Mullally; et al. (Haematologica, 2015)
Clathrin-dependent endocytosis is an essential cellular process shared by all cell types. Despite this, precisely how endocytosis is regulated in a cell-type-specific manner and how this key pathway functions physiologically or pathophysiologically remain largely unknown. PICALM, which encodes the clathrin adaptor protein PICALM, was originally identified as a component of the CALM/AF10 leukemia oncogene. Here we show, by employing a series of conditional Picalm knockout mice, that PICALM critically regulates transferrin uptake in erythroid cells by functioning as a cell-type-specific regulator of transferrin receptor endocytosis. While transferrin receptor is essential for the development of all hematopoietic lineages, Picalm was dispensable for myeloid and B-lymphoid development. Furthermore, global Picalm inactivation in adult mice did not cause gross defects in mouse fitness, except for anemia and a coat color change. Freeze-etch electron microscopy of primary erythroblasts and live-cell imaging of murine embryonic fibroblasts revealed that Picalm function is required for efficient clathrin coat maturation. We showed that the PICALM PIP2 binding domain is necessary for transferrin receptor endocytosis in erythroblasts and absolutely essential for erythroid development from mouse hematopoietic stem/progenitor cells in an erythroid culture system. We further showed that Picalm deletion entirely abrogated the disease phenotype in a Jak2V617F knock-in murine model of polycythemia vera. Our findings provide new insights into the regulation of cell-type-specific transferrin receptor endocytosis in vivo. They also suggest a new strategy to block cellular uptake of transferrin-bound iron, with therapeutic potential for disorders characterized by inappropriate red blood cell production, such as polycythemia vera.